2023
DOI: 10.1186/s12889-023-16630-7
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of suicidal ideation and attempts, and care use and unmet need among suicide-ideators in a Belgian population study

Eva Rens,
Gwendolyn Portzky,
Manuel Morrens
et al.

Abstract: Background Suicidal ideation, or thinking about death and suicide, is common across all layers of society. The aim of this paper is to add to the understanding of suicidal ideation in the general population, as well as help-seeking behaviors and perceived unmet mental health needs among those who report suicidal thoughts. Methods The research is part of a representative population-based survey study of mental wellbeing in Antwerp (Flanders, Belgium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…In a recent study from Belgium, the lifetime-prevalence of suicide attempts seemed to have had an increase from 2.5 % to 6.5%. Prevalence rates were higher in younger people and individuals with a primary educational level and with financial distress [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Belgium, the lifetime-prevalence of suicide attempts seemed to have had an increase from 2.5 % to 6.5%. Prevalence rates were higher in younger people and individuals with a primary educational level and with financial distress [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study including 1202 Belgians aged 15–80 years demonstrated that the prevalence of unmet mental health need increased among individuals with suicidal ideation compared to those without 15 . The proportions of fully and partial unmet need for mental health for suicidal thoughts were 2.3% and 1.3% of total participants, respectively 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increasing rates of suicidal thoughts and behaviors in adolescents have been reported in numerous countries in the aftermath of the COVID-19 pandemic [9]. Data from a Belgian sample reported suicidal ideation in the past few weeks in 15% of adolescents (aged [15][16][17][18][19][20][21][22][23][24][25] [10]. Numbers in Flanders (the Flemish-speaking part of Belgium) are comparable, with a lifetime prevalence for suicidal ideation of 22.3% for 11to 18-year-olds [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the last years brought a decreasing trend in suicide rates, Flanders has seen an increase in suicide in the 15-29-year-old female group [12]. According to a recent study from a Belgian sample, less than 50% of individuals who suffer suicidal ideation sought the help of a health professional in the past 12 months [10]. There is a trend towards earlier onset of suicidal thoughts and behaviors [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation